Complete Atrioventricular Block in Pregnancy - Christin Wigin; Erdwin R Hasibuan; Soetikno Soetikno; Yoga Yuniadi; Liva Wijaya (Indonesian Socety of Obstetrics and Gynecology, 2015)
Objective: Complete heart block is an extremely rare and serious complication in pregnancy. Pregnancy outcome in patients with atrioventricular conduction block are unknown, with only a limited number of case reports published. This paper is aimed to report our case and review the available background literature. Method: Case report. Case: A twentyâ€nine years old primigravida in labor presented at 38 weeks of gestation with referral from the primary health center due to bradycardia and her previous history of cardiac problem. Patient has been diagnosed with total atrioventricular block since 2 years ago. Electrocardiography assessment showed the presence of complete heart block. She was then planned for an emergency Caesarean section and later a temporary transvenous pacemaker was implanted. Conclusion: Management of complete atrioventricular block in pregnancy requires a good team consisting of obstetrician, anesthesiologist and cardiologist. Keywords: atrioventricular, bradycardia, heart block, pacemaker, pregnancy